Density variation of Cs-137 activity in surface soil from the King George Island - Osores, José (2014)
The behavior of radiocaesium from the nuclear tests conducted in the southern hemisphere was evaluated and their behavior was estimated on the floor of King George Island. Based on the findings made by several authors, was estimated at 4.5 years the time of semi-exhaustion for Cs-137 accumulated in the region since 1993.